Ruthenium-Catalyzed Annulation of N-Cbz Hydrazones via C–H/N–N Bond Activation for the Rapid Synthesis of Isoquinolines - Deshmukh, Dewal S.; Bhanage, Bhalchandra M. (Synthesis, 2019)
In this work, N-Cbz hydrazone has been employed as a rarely explored directing group for the synthesis of isoquinolines by annulation with internal alkynes via C–H/N–N activation using Ru catalyst. Additive as well as external oxidant-free rapid protocol has been established for the synthesis of isoquinolines using microwave strategy. Use of non-volatile and biodegradable PEG as a green solvent with lower catalyst loading makes the proposed protocol environmentally benign. Further, higher functional group tolerance and wide substrate scope has been observed under the stated methodology with higher yields.
Keywords: C–H/N–N activation; ruthenium; microwave-assisted; isoquinolines; annulation; hydrazones